Odpowiedzi

Najlepsza Odpowiedź!
2010-01-03T15:25:15+01:00
X+3y=3
x-y=5

x+3y = 3
-y=5-x / * -1

x+3y=3
y=x-5

x+3(x-5)=3
y=x-5

x+3x-15=3
y=x-5

4x=18 / 4
y=x-5

x=4,5
y=-0,5





2x-y=10
x=5y=-17

-y=-2x+10 / * -1
x+5y=-17

y=2x+10
x+5 ( 2x - 10) = -17

y=2x-10
x+10x - 50 = -17

y=2x-10
11x = 33 / 11

y= -4
x=3



4a-2 = b
3a + 7b = 1,5

-b = -4a + 2 / *-1
3a + 7b = 1,5

b= 4a - 2
3a + 7b = 1,5

b = 4a - 2
3a +7 ( 4a - 2) = 1,5

b=4a - 2
3a+28a - 14 = 1,5

b = 4a - 2
31a=15,5 / 31

b=0
a=0,5
35 3 35